LITERATURE REVIEW QUALITY IN INDONESIAN GUIDANCE AND COUNSELING RESEARCH: IMPLICATIONS FOR SDGS-ALIGNED EVIDENCE-BASED PRACTICE - Muhammad Buchori Ibrahim; Hardiansyah Hardiansyah; Asroruddin Lubis (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2026)
Despite the proliferation of guidance and counseling (BK) research in Indonesian higher education, prior studies reveal a persistent gap: literature review practices remain largely descriptive, failing to generate conceptual synthesis or connect empirical findings to evidence-based counseling models aligned with SDGs Goal 4 (Quality Education) and Goal 3 (Good Health and Well-Being). This study aimed to investigate the epistemic nature and functional roles of literature review in Indonesian BK research, with emphasis on its capacity to identify research gaps, strengthen theoretical foundations, and support evidence-based practice development. Employing a qualitative library research methodology, the study systematically gathered and analyzed 25 peer-reviewed sources from Scopus, Web of Science, and DOAJ (2013–2024) through thematic content analysis. Findings reveal six core functions of literature review in BK research: constructing theoretical foundations, identifying research gaps, guiding methodology, preventing duplication, strengthening academic argumentation, and fostering SDGs-aligned evidence-based practice. Crucially, Indonesian BK researchers frequently overlook the conceptual synthesis function, limiting the scholarly impact of their work. This study contributes a contextually grounded framework for literature review practice in Indonesian BK research, with implications for graduate supervision, curriculum design in counselor education, and the advancement of culturally responsive, globally relevant counseling science.